Root Cause Failure Analysis pada Shutoff Hot Damper Mill Di Pt. Indonesia Power Unit Jasa Pembangkitan Jawa Tengah 2 Adipala - Fitri Wijayanti; Nadiyatul Fadhila (Politeknik Negeri Jakarta, 2022)
PT Indonesia Power Unit Power Generation Services Central Java 2 Adipala is one of the suppliers of electrical energy on the islands of Java, Madura and Bali. The main components of PLTU Central Java 2 Adipala are Boilers, Steam Turbines and Generators. The combustion system in the heating process in the boiler requires air, fuel, and heat. Coal as fuel is supplied from coal handling and distributed to the bunker and then through the coal feeder to the Pulvarizer/Mill before going to the combustion chamber. At the time of milling there is a drying, distribution and separation process of coal with foreign objects carried from the mining process so that the coal entering the combustion chamber meets specifications. The milling process is carried out with the help of a Primary Air Fan (PAF) to suck air into the Mill/Pulvarizer. Before entering the Mill/Pulvarizer, the cold primary air and hot primary air are held by the Shut Off Damper, which functions to open and close the PAF airflow to the Mill/Pulvarizer. In the process, there is a possibility of damage/failure from the Shut Off Damper so that the continuity of the process at the Mill/Pulvarizer is disrupted. For this reason, it is necessary to analyze the damage/failure to the Shut Off Damper and solutions